Determination of Influence Levels of Natural Factors Affecting Infiltration and Runoff: A Case Goksu Basin - Fatih Karaosmanoglu (Indonesian Journal of Agricultural Research, 2021)
Water is an indispensable element for human and other living life to live.  Therefore, in any river basin, it is very important to calculate the hydrological cycle parameters such as evaporation, infiltration, and runoff, and to determine the level of influence of natural factors affecting this process. In this study, In Goksu Basin, it is aimed to determine the effect levels of natural criteria such as lithology, soil, land use/cover, soil cover (ndvÄ±), slope, aspect, on infiltration and runoff. In the hydrological model developed for this purpose, natural criteria, digitization formula, ArcGIS based analytical hierarchy (AHP) model program were processed and their effect levels were revealed. According to this result, infiltration and runoff values are close to each other; Lithology 57.1%, soil 12.9%, land use/soil cover 18.4%, slope and aspect between 5.1% and 6.4% were determined. As a result of the model application, the total infiltration and flow amounts of 407.1 mm calculated with the converted real infiltration and runoff coefficients were correlated with the current height of 429.2 mm. It was found to be quite successful at 0.95.